Apropriação de novas mídias por estudantes universitárias - Costa, Adriana Conceição Silva (2013)
It is an investigation that seeks to reveal, record and analyze the process of appropriation and use of digital media by university students, aged between 40 and 60 years. Interested in studying how changes are perceived in the educational sphere for students Whois have gone through liberal/traditional school, ie, effected the first contact with technological devices media as adults, in the university. This investigation sought to contribute to the knowledge on the use of new learning strategies imposed by digital media by recording and analyzing the reports surveyed sample. Allowed to know the cultural universe of these women, revealing the context in which receive mediated messages and uses that maré these learning strategies within their daily academic life. Gathered in this work, reflexions guided by studies of media reception and role played by digital media as builders images and facilitators in knowledging acquisitions, it was chosen to work two main theorical notions: communication media and digital inclusion. As the research methodology, it was used the exploratory descriptive technical together with other appropriate tecniques. In ordem to approach the problem can be observed two phases: a quantitative one, which was used an investigative procedure, a survey data with closed questions; and a qualitative phase, which was used to collect data through a diary from situations encountered in the classroom. The main objective of analyzing how digital media are received, appropriated and used by university women has been fulfilled and it is remarkable that they access with dificulty and can not be considered included digitally. The results show that the problem of these agents is not the access, there are was of appropriation of digital media offered at IES, and it was possible to note that they seek to integrate to the technological world, and they even have devices that can insert them on this world. Insertion in cyberculture sets up the ability to find a favorable way to be aware of reality and production of knowledge and liberating and dignifying practices, in this case refers to an appropriation of citizenship through the field of technological devices offered as a perspective that they can interact